PENGARUH KOMPETENSI, KOMPENSASI DAN LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA PEGAWAI PADA PT. BANK NEGARA INDONESIA (PERSERO) Tbk KANTOR CABANG UTAMA PALU - Aksinapang, Siliatang; Bachri, Syamsul; Azis, Idris (Katalogis, 2018)
The study aims to determine and analyse simultaneous and partial influence of competency, compensation, and non-physical work environment on performance of employees at PT. Bank Negara Indonesia (Persero) Tbk, Palu Headquarter Office. Respondents include 112 employees and data is analyzed with multiple linear regressions analysis version SPSS 16. The result confirms that competency, compensation, and non-physical work environment simultaneously have a significant influence on performance of employees at PT. Bank Negara Indonesia (Persero) Tbk, Palu Headquarter Office. Competency has a significant influence on performance of employees at at PT. Bank Negara Indonesia (Persero) Tbk, Palu Headquarter Office;compensation has a significant influence on performance of employees at PT. Bank Negara Indonesia (Persero) Tbk, Palu Headquarter Office; non-physical environment has a significant influence on performance of employees at at PT. Bank Negara Indonesia (Persero) Tbk, Palu Headquarter Office.